Entrelaçando masculinidades e juventudes no Portal de Periódicos CAPES entre 2000 e 2017 - Oliveira, Francis Fonseca (2018)
Men’s studies are studies of feminist matrix on masculinities that analyze the relations of gender and its intersectionalities. Nowadays, there is an increase in academic productions that problematize male positions and the reinforcement of hegemonic-homophobic-misogynist norms which bring the debates to a pro-feminist agenda. Aiming to analyze how masculinities and youths are being stated in scientific productions and which intersectionalities happen between them, it makes itself important to recognize the productions in the local, regional and global scenarios. For this, we composed two chapters of problematization on the thematic of juvenile masculinities. In the first one, we approached theoretically the men’s studies and the youths in the present time making use of inspirations in diverse areas of knowledge, like Cultural and Gender Studies and Critical Social Psychology. In chapter two, we discussed the construction of the contemporary scenario through a state of art of studies of masculinities and juvenile in the CAPES Periodic Portal platform, from 2000 to 2017. The results found point to a growing discussion of the studies on young men in Brazil and Latin America, and that the productions are presented, mainly, in areas of the human and social sciences. The publications found (176) were discussed in six categories, which pointed to a discussion of gender in the construction of masculine identities being articulated by various social regulatory instances, stage for legitimation or processes of rupture of hegemonic masculinity. The works found reflect an intersectional discussion on discursive reproductions of hegemonic masculinity as a juvenile identitary model that, performatively, fabricates social hierarchizations. The presence of multiple masculine juvenile identities and the way they articulate themselves in these works shows the effort of studies of feminist matrix in the discussion on the plurality of the masculinities juveniles. Due to the timid appearing of works in the local reality, we propose the need to think about such works, as well as to carry out research in the local context about young people and their multiple experiences of masculinities (including trans) and intersectionalities, in the smallest Brazilian state.